TRANSLATION OF EXPRESSIVE SPEECH ACTS BY PROTAGONIST AND ANTAGONIST CHARACTERS IN THE WITCHER SERIES - Septiaji, Faisal; Nababan, Mangatur Rudolf; Santosa, Riyadi (Universitas Islam Sumatera Utara (UISU), 2025)
This study examines the translation of expressive speech acts in the Netflix series The Witcher, focusing on the protagonist Geralt of Rivia and the antagonist Cahir Mawr Dyffryn. Expressive speech acts—such as apology, gratitude, condolence, lament, congratulation, protest, and praise—play a crucial role in conveying emotions and shaping character identity. A total of 158 utterances were analyzed from English–Indonesian subtitle pairs using qualitative descriptive methods, supported by translation quality assessment based on accuracy, acceptability, and readability. Findings reveal distinct pragmatic patterns: Geralt frequently uses empathetic expressions like protest, apology, and regret, reflecting moral engagement and interpersonal sensitivity, while Cahir predominantly employs praise and boasting, emphasizing authority and self-image. Analysis of 700 translation instances shows that established equivalence (56.14%) and variation (17.29%) were the most common techniques, supporting naturalness, readability, and cultural appropriateness. Techniques such as modulation, paraphrase, amplification, and compensation were applied to preserve pragmatic force and emotional nuance. Overall, translation quality was high, with mean scores of 2.84 (accuracy), 2.76 (acceptability), and 2.89 (readability). This study contributes a novel perspective by linking expressive speech acts with character function and translation strategies in subtitling. The findings emphasize the importance of selecting translation techniques that maintain pragmatic intent, emotional impact, and character portrayal, offering guidance for audiovisual translators and informing future research on cross-cultural narrative translation.